Federalism and the significance of Governmental Agencies and of organizational Experience at the time of country’s Crisis: Tracing the Emergency Medication Response System of the Covid-19 Pandemic (Voice of Teacher, 2023)
This research has focused on the emergency response based on the section 1135 emergency waivers which were devised as instruments for policymakers to swiftly enhance the capacity of the health system in times of disaster. By providing flexibilities in regulations, administration, and payment models during the COVID-19 pandemic, states could be better prepared for a surge in hospitalizations and protecting the life of those who were in the emergency response to take care through the process of the hospitalization on time. It employs a Time-to-Event analytical framework to identify key factors influencing the adoption of a state’s 1135 Waiver request. In the primary model, the event of interest is a state making a request for a Section 1135 Waiver, and the dependent random variable is the time elapsed between the disaster proclamation and the state’s request date. The primary independent variable is binary, indicating whether a state has previously sought Section 1135 Medicaid flexibilities during past emergencies. The study stands as the inaugural attempt to pinpoint notable factors influencing Section 1135 Waivers. If efficiency is gauged by swifter requests, then the effectiveness of emergency waivers during the COVID-19 pandemic is predominantly shaped by institutional and external factors. it has revealed that the effective organizational and institutional tasks in the federalism during the emergency would assist to address the issues of the national crisis as it has been explained by the 1135 Waivers as the sample study for further information to the concerned stakeholders not merely in the advanced nation as of the United States of The America but even to the backward countries as of the Asian continents.